2017
DOI: 10.3390/ijms18102226
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Hypothalamic-Pituitary-Adrenal Axis Measures and Inflammatory Marker Correlates in Major Depressive Disorder

Abstract: Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and inflammatory systems is a consistent finding in patients with Major Depressive Disorder (MDD). Cortisol is often assessed by measurement of the cortisol awakening response (CAR) and/or diurnal cortisol levels. Some methods of cortisol measurement overestimate cortisol concentration due to detection of other glucocorticoids including the relatively inert cortisone, therefore this study aimed to assess the presence of both cortisol and cortisone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 65 publications
0
30
0
1
Order By: Relevance
“…A similar profile with higher morning cortisol levels without differences in evening cortisol was described in patients with anxiety disorders and comorbid depressive disorder ( 6 , 32 ). Higher cortisol levels have been found in depressed individuals ( 33 , 34 ). Even though a steeper diurnal cortisol slope was associated with numerous other favorable mental and physical health outcomes and is therefore typically interpreted as salubrious profile, a recent meta-analysis reported a trend toward a steeper diurnal slope, driven by elevated morning cortisol, in patients with anxiety disorders ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar profile with higher morning cortisol levels without differences in evening cortisol was described in patients with anxiety disorders and comorbid depressive disorder ( 6 , 32 ). Higher cortisol levels have been found in depressed individuals ( 33 , 34 ). Even though a steeper diurnal cortisol slope was associated with numerous other favorable mental and physical health outcomes and is therefore typically interpreted as salubrious profile, a recent meta-analysis reported a trend toward a steeper diurnal slope, driven by elevated morning cortisol, in patients with anxiety disorders ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“… 35 A series of studies also provided support for the role of inflammatory factors in the development of IPSD. 39 41 Under the influence of repeated inflammatory stimuli, microglia in the central nervous system can evolve into a source of inflammatory mediators, which may then influence brain neurotransmitter systems and neuronal integrity. 42 Moreover, elevated levels of inflammatory cytokines can also affect the activity of 2,3-dioxygenase, which degrades tryptophan via the kynurenine pathway and ultimately leads to a reduction in the synthesis and availability of 5-hydroxytryptamine.…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a prevalent medical illness that comprises a variety of different symptoms (e.g., depressed mood, anhedonia, changes in appetite and sleeping, loss of energy, somatic symptoms and others). 1 The pathophysiology of MDD is related to several neurobiological changes, including hypothalamic-pituitary-adrenal (HPA) axis malfunction and consequent increase [2][3][4] or decrease [5][6][7] in basal cortisol levels. Previous studies have shown that pharmacological treatment can modulate cortisol levels independently of promoting remission of depressive symptoms.…”
Section: Can Physical Exercise Modulate Cortisol Level In Subjects Wimentioning
confidence: 99%